Transportation and Traffic Theory in the 21<sup>st</Sup> Century 2002
DOI: 10.1108/9780585474601-024
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Freeway Ramp Merging Process Observed During Traffic Congestion

Abstract: This work focuses on modeling vehicle acceleration-deceleration behavior during freeway and ramp merging maneuvers under congested traffic situation. On the Tokyo Metropolitan Expressway, traffic congestion frequently occurs at merging bottleneck sections. There have been only a few research studies concerned with the traffic behavior and characteristics in these situations. Therefore, a three years extensive study has been undertaken to investigate traffic behavior and characteristics during traffic merging p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…One possibility is to use ITS (Intelligent Transport System) facilities such as VMS (variable message sign) or navigation systems ahead of the merging section to inform drivers and guide traffic. Other strategies such as lane closure or post cone installation require experimental data for their implementation, which in most cases is difficult to obtain because of the risks and high costs involved in data collection (Sarvi, 2000a). An alternative to the examination and evaluation of the real traffic conditions is to use simulation experiments to mimic actual traffic scenarios.…”
Section: And Avishai Cedermentioning
confidence: 99%
“…One possibility is to use ITS (Intelligent Transport System) facilities such as VMS (variable message sign) or navigation systems ahead of the merging section to inform drivers and guide traffic. Other strategies such as lane closure or post cone installation require experimental data for their implementation, which in most cases is difficult to obtain because of the risks and high costs involved in data collection (Sarvi, 2000a). An alternative to the examination and evaluation of the real traffic conditions is to use simulation experiments to mimic actual traffic scenarios.…”
Section: And Avishai Cedermentioning
confidence: 99%
“…Based on Figure 6, it could be concluded that drivers start switching their behavior (e.g. car-following) from free flow mode to congested flow mode when they are caught in the queue, and complete the switching when their time in the queue reaches around 15 minutes (comprehensive car-following study is carried out but it lies beyond the scope of present work however, is the subject of other studies summarized in Sarvi et. al.…”
Section: Congestion Forming and Developmentmentioning
confidence: 96%
“…The second decision, which involves the ramp driver searching for and accepting a suitable gap, has been extensively studied for the free-flow merging condition , Daganzo 1981, Makigami et al 1988, Chang and Kao 1991, Ahmed et al 1996, Kita 1999, Kurian 2000. The gap searching and acceptance maneuvers commonly observed under free-flow conditions do not occur under heavy traffic flow conditions, according to a macroscopic study by Sarvi and Kuwahara (1999) and Sarvi (2000). These macroscopic studies found no significant correlation between the acceleration lane length and the maximum flow rate in the merging sections.…”
Section: The Decision Process Of Driversmentioning
confidence: 98%
See 2 more Smart Citations